Symmetry and Electronic Properties of Metallic Nanoclusters - Roduner, Emil (Symmetry (Basel), 2023)
Spherical nanoclusters with countable member atoms and delocalized valence orbitals are superatoms with properties analogous to those of simple atoms. This is reflected, in particular, in their optical spectra and magnetic properties, in a similar sense to transition metal ions and complexes. Clusters can be of low-spin or high-spin with considerable contributions to magnetism by the large cluster orbital magnetic moment. Due to the large radius of the clusters, they can be diamagnetic with an unusually high diamagnetic susceptibility. Gold and platinum, which in the bulk are non-magnetic, show pronounced superparamagnetism associated with their high-spin nature, and the magnetic moment can be trapped in symmetry-breaking environments so that hysteresis pertains far beyond room temperature. A significant deviation from hydrogen-like orbitals results from the shape of the confining potential, which has the effect that the orbital quantum number ℓ is not limited to values less than the principal quantum number n.